2016
DOI: 10.1071/ch15417
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Mace-Like Fe3O4 Nanostructures as a Lithium–Air Battery Cathode Material

Abstract: Mace-like Fe3O4 nanostructures with a length of 200–300 nm and a diameter of 10–30 nm were successfully synthesized via a microemulsion-mediated solvothermal method and used as an electrode catalyst for lithium–air batteries. The results showed that the mace-like Fe3O4 nanostructures were obtained by adjusting the NaOH concentration and reaction temperature, and by adding polyethylene glycol-1000. The growth and assembly mechanism of the mace-like Fe3O4 nanostructures was also discussed. Polyethylene glycol-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Therefore, it could be figured out that Fe 3 S 4 outperforms Fe 3 O 4 as cathode catalyst for Li-O 2 battery, judging from both the electrochemical kinetics and battery performance. When compared with the reported data for Fe 3 O 4 catalysts in literatures, [35][36][37] the specific capacity of Fe 3 O 4 based Li-O 2 battery in this work is about 2.5 times higher as diagramed in Fig. 3d.…”
Section: Resultssupporting
confidence: 71%
“…Therefore, it could be figured out that Fe 3 S 4 outperforms Fe 3 O 4 as cathode catalyst for Li-O 2 battery, judging from both the electrochemical kinetics and battery performance. When compared with the reported data for Fe 3 O 4 catalysts in literatures, [35][36][37] the specific capacity of Fe 3 O 4 based Li-O 2 battery in this work is about 2.5 times higher as diagramed in Fig. 3d.…”
Section: Resultssupporting
confidence: 71%
“…9,10 Lv et al synthesized macelike Fe-based oxide and used it as porous cathode material for LOBs. 11 However, intrinsic electronic conductivity of iron-based oxide is very low, leading to considerable loss of energy density in LOBs; therefore, it should be mixed with inexpensive conducting carbon materials (e.g., carbon nanotubes (CNTs), graphene, and carbon nanofibers (CNFs)). 12−14 For examples, Wu et al synthesized Fe 2 O 3 nanoparticles (NPs) supported by Vulcan XC-72 carbon as LOB cathode and suggested that Fe 2 O 3 coupled with conductive carbon can effectively reduce charge overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, conductive metals, such as cobalt (Co), ruthenium (Ru), and gold (Au), have been introduced as efficient and stable catalysts. However, these catalysts are expensive; thus, their use might be limited in practical level of Li–O 2 cell fabrication. As one of the alternatives to these, iron (Fe)-based catalysts have been employed as an O 2 cathode material because they are cost-effective and abundant in earth’s crust. , Lv et al synthesized macelike Fe-based oxide and used it as porous cathode material for LOBs . However, intrinsic electronic conductivity of iron-based oxide is very low, leading to considerable loss of energy density in LOBs; therefore, it should be mixed with inexpensive conducting carbon materials (e.g., carbon nanotubes (CNTs), graphene, and carbon nanofibers (CNFs)). For examples, Wu et al synthesized Fe 2 O 3 nanoparticles (NPs) supported by Vulcan XC-72 carbon as LOB cathode and suggested that Fe 2 O 3 coupled with conductive carbon can effectively reduce charge overpotential .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been shown to enhance the cell ability to have an initial discharge capacity of 1429 mAh g À1 at 1.5e4.5 V and 100 mA g À1 . In another work, we prepared mace-like Fe 3 O 4 nanostructures using a solvothermal method in cyclohexane/Triton X-100/n-amyl alcohol/water system [26]. The results of chargeedischarge tests based on these nanostructures exhibited a high discharge capacity of 1427 mAh g À1 in ambient air.…”
Section: Applications Of Fe 3 O 4 Microstructures In Libsmentioning
confidence: 99%